Inovasi Sandal Refleksi Berbahan Dasar Sekam Giling sebagai Peluang Usaha Mahasiswa STKIP PGRI Jombang - Muhammad Amirul Aziz; Sukarti Putri Afianti; Muhammad Nafiul Umam; Mecca Puspitaningsari (CERED Indonesia Publishing, 2021)
The goal is to utilize the husk waste which is still very lacking, the abundant husk waste is mostly just piled up around the mill. There are also those who sell at very low prices. The husks are found in many villages. One of them is Genukwatu Village.Methods used 1. Survey of Tool and Material Availability and Reflection Product Competitors, 2 Creating Sarekamling Product Concepts and Designs, 3.Creating Virtual Product Marketing Concepts. If successfully made, this product can reduce husk waste which has been underutilized so far. In addition, this product will have a great opportunity to be developed because this product is a reflection sandal product that has several advantages over other reflection products. Sarekamling is a new breakthrough for reflective sandals using the basic material of milled husks. This sandal is combined with blackjade stone which has various health benefits. This product is expected to be an alternative health product that can be used at any time without pain but can be obtained at an affordable price. This product is pegged at a price of IDR 106,000.00.